Connexins in Lung Cancer and Brain Metastasis - Luo, Kai-Jun; Chen, Chang-Xu; Yang, Jia-Peng; Huang, Yun-Chao; Cardenas, Eduardo R.; Jiang, Jean X. (Frontiers in Oncology, 2020)
Connexins (Cxs) are involved in the brain metastasis of lung cancer cells. Thus, it is necessary to determine whether gap junction-forming Cxs are involved in the communication between lung cancer cells and the host cells, such as endothelial cells, forming the brain–blood-barrier, and cells in the central nervous system. Data from multiple studies support that Cxs function as tumor suppressors during lung cancer occurrence. However, recent evidence suggests that during metastasis to the brain, cancer cells establish communication with the host. This review discusses junctional or non-junctional hemichannel studies in lung cancer development and brain metastasis, highlighting important unanswered questions and controversies.